Obama at Mona : youth leaders interact with President Obama at historic UWI town hall meeting (2015)
Presents brief note on the town hall meeting at the UWI Mona Campus with visiting US President Barack Obama and Young Leaders of the Americas Initiative.
Keywords: UNITED STATES